2016
DOI: 10.3823/2082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Support on Quality of Life, CD4+ T-cell Count and Viral Load of People Living With HIV/AIDS

Abstract: Background: Social support is an information leading the subject to believe that is cared, esteemed, and is member of a network of mutual obligations. Studies showed that absence of social support could increase vulnerability to diseases. The purpose of study was to analyze the effect of social support on quality of life (QOL), CD4+ T-cell count and viral load of people living with HIV/AIDS (PLWHA) in ambulatorial service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A recent study done in Brazil showed patients with satisfactory social support had a significant reduction in VL. 6 It was a cohort study with 1-year follow-up in which they analysed the effect of social support on quality of life, CD4 count and VL of PLHIV. They also found that in patients with unsatisfactory social support, there was no significant reduction in their VL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study done in Brazil showed patients with satisfactory social support had a significant reduction in VL. 6 It was a cohort study with 1-year follow-up in which they analysed the effect of social support on quality of life, CD4 count and VL of PLHIV. They also found that in patients with unsatisfactory social support, there was no significant reduction in their VL.…”
Section: Introductionmentioning
confidence: 99%
“…Cunha et al in Brazil, assessing the effect of social support on quality of life, CD4 and VL, found that those with a satisfactory social support had significant reduction in VL 6. Randomised control trials done by Cuong et al8 in Vietnam and Nachega et al9 in SA, assessing impact of peer support on virologic outcome, have both found no association between intervention and control group; whilst another RCT done by Kenya et al, assessing impact of CHW on clinical outcome (CD4 and VL), found that intervention group had significant lower VL than control.…”
mentioning
confidence: 99%